The Urgency of Instilling the Character of Trustworthiness in Students in an Effort to Form Muslim Personalities Case Study at Wangkanapi State Elementary School - Hasan, Meily Hasniar Kartika; Rahim, Abdul; Sulasri, Sulasri (Jurnal Ilmu Pendidikan dan Humaniora, 2025)
Amanah is a moral value that reflects honesty, responsibility, and trust in carrying out tasks and obligations. Therefore, instilling this trait from an early age is very important to shape the character of students with integrity. This study aims to analyze the importance of instilling the trait of amanah in Wangkanapi Elementary School, Baubau City, and to identify effective methods for its implementation in the school environment. The research method used is a qualitative approach with observation techniques, interviews, and literature studies to collect data from students, teachers, and school policies related to character formation. The results of the study show that students who understand and are accustomed to the trait of amanah tend to be more responsible, honest, and able to establish good social relationships. In addition, the role of teachers, the school environment, and parental involvement greatly influence the success of instilling the value of amanah. Effective strategies include habituation in daily activities, role models from teachers and parents, and integration of amanah values in the curriculum. Therefore, cooperation between schools and families is very necessary to build student character based on amanah values from an early age.